Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2008
DOI: 10.1124/jpet.108.140806
|View full text |Cite
|
Sign up to set email alerts
|

Calcium Sensitization in Human Esophageal Muscle: Role for RhoA Kinase in Maintenance of Lower Esophageal Sphincter Tone

Abstract: A rise in intracellular-free calcium ([Ca 2ϩ ] i ) concentration is important for initiating contraction of smooth muscles, and Ca 2ϩ sensitization involving RhoA kinase can sustain tension. We previously found that [Ca 2ϩ ] i was comparable in cells from the esophageal body (EB) and lower esophageal sphincter (LES) muscles, despite the fact that the LES maintains resting tone. We hypothesized that Ca 2ϩ sensitization contributes to contraction in human esophageal muscle. Tension and [Ca 2ϩ ] i … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
25
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(33 citation statements)
references
References 39 publications
(80 reference statements)
6
25
2
Order By: Relevance
“…Several lines of evidence support the predominance of the RhoA/ROCK pathway in the IAS as follows: The maximal decrease in the IAS tone is significantly higher following the ROCK inhibition with Y 27632 (80%) compared with the PKC inhibition with Gö 6850 and calphostin C (27 and 19%, respectively). These data are similar to the previous data in the rat IAS (22,23,28) and intact human and cat lower esophageal sphincter smooth muscle (15,21,31). Clamping experiments performed in the present studies further show that, following maximal decrease in the IAS tone with ROCK inhibition, PKC inhibition produces a limited effect.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Several lines of evidence support the predominance of the RhoA/ROCK pathway in the IAS as follows: The maximal decrease in the IAS tone is significantly higher following the ROCK inhibition with Y 27632 (80%) compared with the PKC inhibition with Gö 6850 and calphostin C (27 and 19%, respectively). These data are similar to the previous data in the rat IAS (22,23,28) and intact human and cat lower esophageal sphincter smooth muscle (15,21,31). Clamping experiments performed in the present studies further show that, following maximal decrease in the IAS tone with ROCK inhibition, PKC inhibition produces a limited effect.…”
Section: Discussionsupporting
confidence: 81%
“…The present data show a predominant role of RhoA/ROCK over PKC, similar to that of intact IAS in other animals (11) and other spontaneously tonic intact smooth muscle of the LES in humans and animals (15,21,31). These data are, however, Ϫ5 M cause significant decreases in the IAS tone (*P Ͻ 0.05; n ϭ 4).…”
Section: Gö Göcontrasting
confidence: 49%
“…In contrast to the basal tone in human and cat lower esophageal sphincter, ACh-and EFS-induced phasic contraction in the esophageal body is primarily mediated by PKC (12,25,37). Similar conclusions were drawn by the inhibition of carbachol-induced contraction of urinary bladder by PKC inhibitor (7).…”
Section: Discussionsupporting
confidence: 64%
“…[In contrast to the phasic activity in RSM, a number of studies have shown that basal tone in the lower esophageal sphincter and IAS in humans and animals is mediated primarily via the RhoA/ROCK pathway (25,30,32,37).] The present data also show selectivity of the effects of PKC and ROCK inhibitors on the respective pathways.…”
Section: Discussioncontrasting
confidence: 38%
“…In the LES, ROCK inhibitors have been shown to produce full relaxation of the basal tone in human and various animal species, while PKC inhibitors have only limited effects on LES basal tone. 17,80 These studies suggest that a mechanism of Ca 2+ sensitization mediated by the RhoA/ROCK pathway plays an important role in the basal tone in the LES, although MYPT1 and CPI-17 phosphorylation in the LES has not been measured. Interestingly, the proton pump inhibitor pantoprazole inhibited MYPT1 T853 phosphorylation evoked by CCh in gastric and LES tissue, suggesting that it may also be a ROCK inhibitor, although it had no effect on constitutive MYPT1 or CPI-17 phosphorylation.…”
Section: Cpi-17 and Mypt1 Are Constitutively Phosphorylated In Gastromentioning
confidence: 99%